2017
DOI: 10.1155/2017/5725340
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Cell Damage Analysis for Single- and Multifocus Coherent Anti-Stokes Raman Scattering Microscopy

Abstract: In this study, we investigated photo-induced damage to living cells during single-and multifocus excitations for coherent antiStokes Raman scattering (CARS) imaging. A near-infrared pulsed laser (709 nm) was used to induce cell damage. We compared the photo-induced cell damage in the single-and the multifocus excitation schemes with the condition to obtain the same CARS signal in the same frame rate. For the evaluation of cell viability, we employed 4′,6-diamidino-2-phenylindole (DAPI) fluorophores that predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, with CARS microscopy, a number of questions remain as to whether: (i) live-imaging using CARS microscopy is fully non-invasive; (ii) cell development remains unaltered; and (iii) the cells remain viable and robust for further use in clinical applications following live-imaging with CARS microscopy. Studies have reported on thresholds of photo-induced cell damage by CARS microscopy, commonly by visualising direct cell morphological changes 13 , and detecting formation of apoptotic membrane protrusions 14 , or by analysing and comparing nuclear staining between damaged and non-damaged cells after laser exposure 15 . The induced damage and changes are obvious at the levels of damage thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…However, with CARS microscopy, a number of questions remain as to whether: (i) live-imaging using CARS microscopy is fully non-invasive; (ii) cell development remains unaltered; and (iii) the cells remain viable and robust for further use in clinical applications following live-imaging with CARS microscopy. Studies have reported on thresholds of photo-induced cell damage by CARS microscopy, commonly by visualising direct cell morphological changes 13 , and detecting formation of apoptotic membrane protrusions 14 , or by analysing and comparing nuclear staining between damaged and non-damaged cells after laser exposure 15 . The induced damage and changes are obvious at the levels of damage thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…This figure shows that the SRS image of the lipid droplet is successfully obtained at the resonance Raman shift. For future works, SRS lock-in CMOS pixel array will be used in conjunction with multi-focus irradiation where less photo-damage is achieved [ 18 , 19 ]. Imaging time can be drastically improved and imaging at video rate using small CMOS image sensor could be achieved.…”
Section: Measurement Results and Discussionmentioning
confidence: 99%
“…In single beam irradiation method, higher laser power is needed in order to achieve high-speed imaging. Considering the photo-damage to the biological sample is mainly induced by multiphoton events, which is proportional to the peak power of the incident laser, higher laser power increases the potential of greater photo-damage to the biological samples [ 18 , 19 , 28 ]. For single-focus and multi-focus systems obtaining signals at the same frame rate, multi-focus imaging requires longer exposure time but lesser peak laser power on each point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations